Genetic diversity of Fusarium oxysporum f. sp. cubense in East and Central Africa - Karangwa, P.; Mostert, D.; Ndayihanzamaso, P.; Dubois, T.; Niere, B.; Felde, A. zum; Schouten, A.; Blomme, Guy; Beed, Fenton D.; Viljoen, Altus (Scientific Societies, 2018)
Banana Fusarium wilt is a major production constraint globally and a significant threat to the livelihoods of millions of people in East and Central Africa (ECA). A proper understanding of the diversity and population dynamics of the causal agent, Fusarium oxysporum f. sp. cubense (Foc), could be useful for the development of sustainable disease management strategies for the pathogen. The current study investigated the diversity of Foc in ECA using vegetative compatibility group (VCG) analysis, PCR-RFLPs of the ribosomal DNA’s intergenic spacer region, as well as phylogenetic analysis of the elongation factor-1α gene. Six VCGs (0124, 0125, 0128, 01212, 01220, and 01222), which all belong to one lineage (Foc lineage VI), were widely distributed throughout the region. VCGs 0128 and 01220 are reported for the first time in Burundi, the Democratic Republic of Congo (DRC), Rwanda, Tanzania, and Uganda, while VCG 01212 is reported in the DRC and Rwanda. Isolates that did not belong to any of the known VCGs were identified as Foc lineage VI members by phylogenetic analysis and may represent novel VCGs. CAV 2734, a banana pathogen collected in Rwanda, clustered with nonpathogenic F. oxysporum isolates in lineage VIII. Results from this study will contribute significantly toward the implementation of banana Fusarium wilt disease management practices in the region, such as the restricted movement of infected planting material and the selective planting of resistant banana varieties.